Geletterd Zeeland - De la Ruë, Pieter 1695-1770 (Middelburg Callenfels, 1741)
The Middelburg dignitary and poet Pieter de la Rue made his name mainly as a writer of local history. In Geletterd Zeeland he recorded the biographies of Zeeland's writers, scholars and artists. Two years later, this work was followed up with Geletterd en Staatkundig and Heldhaftig Zeeland, in which not only the artistic and intellectual leaders of the region are honoured with a life sketch, but also its military heroes. De la Rue was a frequent presence in the Zeeland literary milieu of his time.
Originally published in 1734
Bound in white vellum
verdeeld in drie afdeelingen, bevattende in zig de schryvers, geleerden en kunstenaars, uit dien staat geboortig, met bygevoegd levensverhaal der voornaamsten onder dezelve. Tweede druk, met eenige noodige veranderingen en ettelyke vermeerderingen zynde hieragter ook geplaatst de byschriften op de groote en smalle steden van Zeeland
Keywords: 18th Century (1701-1800); Biography; Poetry; Literature; Zeeland (Netherlands); bibliotheek; Barlaeus, C; boekoplage; beiaard; Boxhorn; Burman, P; Cats, J; muziek (algemeen); compositieloon; op de wijze van; dansen; orgels in Nederland; Descartes; dichteres; Pels, A; plagiaat; Erasmus; tabak; thee; toneel; Groot, H. de; Valerius, A; Verkolje, N; Heinsius, D; Heinsius, N; Hooft, P.C.; Houbraken, J; Huygens, C; Vondel, J. van den; Vossius, G.J.; Vossius, I; Jordaens, J; Willem III; wonderkind; rederijkers; koffie; Revius, J; Roemer Visscher, Anna; Rue, P. de la; salaris; Scaliger, J; Secundus, J; mecenas; Meursius, J; motet; anonymus; Baudartius, G; Beccius, J; Beeckman, I; Brandt, G; Brune, J. de; Bustijn, P; Buysero, D; chocolade; Coccejus, J